Application of QSAR Analysis and Different Quantum Chemical Calculation Methods in Activity Evaluation of Selected Fluoroquinolones - Kawczak, Piotr; Bober, Leszek; Bączek, Tomasz (Combinatorial Chemistry & High Throughput Screening, 2018)
Background: A set of antibiotic fluoroquinolones with confirmed antimicrobial activity were analyzed with the use of two types of quantum chemical calculation methods and quantitative structure-activity relationships (QSAR). Objective: The purpose of this study was to demonstrate the common and differentiating characteristics of the above-mentioned chemical compounds alike physicochemically as well as pharmacologically based on the quantum chemical calculations and microbiological activity data. Methods: During the study PCA and MLR analysis were performed, as the types of proposed chemometric approach. The semi-empirical level of in silico molecular modeling was performed for calculations of molecular descriptors. Results: QSAR models were proposed based on chosen descriptors. The relationship between the structure and microbiological activity and physicochemical parameters data was able to class and describe them with the use of statistically significant molecular descriptors. Conclusion: The applied chemometric approaches revealed the influential features of tested structures responsible for the antimicrobial activity of analyzed compounds.
Keywords: Fluoroqinolones